Numerical Simulation of Depth Tracking Control of an Underwater Towed System Coupled with Wave–Ship Interference - Xianyuan Yang; Jiaming Wu; Quanlin Li; Haiyan Lv (Journal of Marine Science and Engineering, 2021)
This paper presents a numerical study of the depth tracking control for an underwater towed system under wave–ship interference condition. To overcome the laminations of ignoring the hydrodynamic factors and wave–ship interference in the existing simulation model for the depth tracking operation of the underwater towed system, a numerical model combining the control system with the computational fluid dynamics (CFD) method based on the overset mesh technique is explored and constructed; the influence of towing ship and head waves is introduced into the numerical analysis of the underwater towed system; a depth control system based on the center of gravity adjustment is proposed and its control characteristics are discussed. The fluid motion around the towed vehicle and the towing ship is governed by the Navier–Stokes equations, and the overset mesh technique is applied for the numerical solution of the equations. The towing cable connecting the towed vehicle and towing ship is governed by the quasi-steady-state catenary equations. The depth tracking controller adjusting the longitudinal position of a shifting weight is constructed based on the proportional–integral–derivative (PID) algorithm. The simulation results show that the numerical simulation system is practicable, and the depth tracking control system is feasible, effective, and robust.